A new pulse-width modulation (PWM) scheme for modular structured multilevel voltage source inverter - Aziz, J. A.; Salam, Zainal (Taylor & Francis, 2004)
This work proposes a new switching scheme for a particular multilevel topology, known as the modular structured multilevel inverter (MSMI). The proposed scheme is based on symmetric regular sampled unipolar PWM, with multiple modulating waveforms and a single carrier. Mathematical equations that define the PWM switching instants are derived. These equations are suitable for digital implementation. An experimental five-level MSMI test-rig is built to implement the proposed algorithm. The derived equations are implemented by a low-cost fixed-point microcontroller. Several tests to quantify the performance of the inverter under the proposed modulation scheme are carried out.